The effectiveness of Eye Movement Desensitization and Cognitive Reprocessing Intervention (EMDR) on Improving the Quality of Life and Reducing the Guilt Feeling in Parents of Children with Low-Functioning Autism - سعید رضایی; مهدی خانجانی (فصلنامه خانواده پژوهی, 2017)
The present study was to evaluate the effects of eye movement desensitization and cognitive reprocessing intervention (EMDR) on improving the quality of life and reducing the guilt feelings in parents of children with low-functioning autism. The research was set up in an experimental pretest-posttest design with a control group and follow up. As sample of study, 16 pairs of parents (mother and father) of children with low-functioning autism who had referred to autism rehabilitation centers, were departed randomly to two experimental (8 couples) and control (8 couples) groups. The World Health Organization Quality of Life Questionnaire (WHO-QOL) and the Guilt Questionnaire (Kugler and Jones, 1998) were used for data collection. The EMDR intervention program was implemented in 10 two-hour sessions during one month for the experimental group. After 45 days, the follow-up test was conducted on the experimental group. Data were gathered and analyzed using a mixed-design analysis of variance model. The results showed a statistically signifycant (P = 0/5) effectiveness of the EMDR intervention in improving the quality of life and reducing the guilt feelings of parents of children with low- functioning autism.